2008
DOI: 10.1002/cjoc.200890294
|View full text |Cite
|
Sign up to set email alerts
|

An HPLC Method for Determination of a New Diorganotin(IV) Benzohydroxamate in Rat Plasma and Its Application to Pharmacokinetic Studies

Abstract: n-Bu) 2 Sn{4-ClC 6 H 4 C(O)NHO} 2 ] (DBDCT) is a new diorganotin(IV) benzohydroxamate which shows high in vivo antitumor activity with relative low toxicity. An HPLC method for the determination of diorganotin(IV) benzohydroxamate (DBDCT) was first validated in the pharmacokinetic studies in plasma. The rat plasma was deproteinized with methanol that contained acetanilide as the internal standard and then separated. The HPLC assay was carried out using a Diamonsil ODS (4.6 mm×200 mm, 5 µm) column. The mobile p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…100 µl acetanilide (2.5 µg ml −1 ) and 100 µl methanol were added to 100 µl samples, respectively. After the samples were vortexed for 3 min, the mixture was centrifuged at 13 000 × g for 5 min at 4 °C and the supernatant was extruded through membranes of 0.45 µm pore size …”
Section: Methodssupporting
confidence: 64%
See 3 more Smart Citations
“…100 µl acetanilide (2.5 µg ml −1 ) and 100 µl methanol were added to 100 µl samples, respectively. After the samples were vortexed for 3 min, the mixture was centrifuged at 13 000 × g for 5 min at 4 °C and the supernatant was extruded through membranes of 0.45 µm pore size …”
Section: Methodssupporting
confidence: 64%
“…Compared to free DBDCT, DBDCT‐L had lower Cl. Our previous studies showed that the free DBDCT was eliminated quickly in blood, 2 h later . In this study, according to the data shown above, DBDCT‐L obviously prolonged the residence time and improved the concentration of DBDCT in the blood circulation system.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…In the present study, we investigated the mechanisms by which DBDCT induce apoptosis in SGC‐7901 cells. DBDCT has been shown to have high in vivo antitumor activities, which have been reported to be identical to, or even higher than that of cisplatin 36, 37, and has been shown to induce the apoptosis of human SGC‐7901 cells. Our results show that DBDCT inhibited the growth of SGC‐7901 cells, caused apoptotic DNA fragmentation, blocked cell‐cycle progression in G 1 and/or G 2 –M, and induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%